STATE-OWNED RURAL BANK PERFORMANCE: DO GOVERNMENT OWNERSHIP AND CORPORATE GOVERNANCE UNIQUENESS MATTER? - Noerdin, Azilsyah (JURNAL AKUNTANSI DAN AUDITING, 2016)
It has been widely recognized that ownership structure has an impact on firm performance. This paper examines whether rural banks owned by government have poorer performance than those owned by private parties with the emphasis on corporate governance uniqueness of state-owned rural banks. 42 rural banks in Indonesia has been selected as the sample. MANOVA test is used to investigate the difference performance between the two types of the rural banks. The results show that state-owned rural banks perform poorer than their privately-owned counterparts. It is indicated by lower ROA ratio and higher OEOI and NPL ratios. The important implication of this finding suggets that government ownership impede boards of rural banks to implement good corporate governance practices in order to improve their banks performance.